2018
DOI: 10.1016/j.brainres.2018.08.023
|View full text |Cite
|
Sign up to set email alerts
|

Hyperfibrinogenemia-mediated astrocyte activation

Abstract: Fibrinogen (Fg)-containing plaques are associated with memory loss during various inflammatory neurodegenerative diseases such as Alzheimer’s disease, multiple sclerosis, stroke, and traumatic brain injury. However, mechanisms of its action in neurovascular unit are not clear. As Fg is a high molecular weight blood protein and cannot translocate far from the vessel after extravasation, we hypothesized that it may interact with astrocytes first causing their activation. Cultured mouse cortical astrocytes were t… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

3
24
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
6

Relationship

3
3

Authors

Journals

citations
Cited by 14 publications
(27 citation statements)
references
References 81 publications
3
24
0
Order By: Relevance
“…The data showed that Fg was co-localized and thus strongly associated with astrocyte ICAM-1 and PrP C , suggesting that it is possibly binding to these receptors on the surface of astrocytes. This is the first time a Fg specific interaction with astrocytes was visualized, confirming our previous finding that Fg could be associated with ICAM-1 [ 21 ] and PrP C with high specificity [ 16 , 36 , 39 ]. Thus, the increased respective PLA signals can be the result of a Fg interaction with over-expressed astrocyte ICAM-1 and PrP C .…”
Section: Discussionsupporting
confidence: 88%
See 4 more Smart Citations
“…The data showed that Fg was co-localized and thus strongly associated with astrocyte ICAM-1 and PrP C , suggesting that it is possibly binding to these receptors on the surface of astrocytes. This is the first time a Fg specific interaction with astrocytes was visualized, confirming our previous finding that Fg could be associated with ICAM-1 [ 21 ] and PrP C with high specificity [ 16 , 36 , 39 ]. Thus, the increased respective PLA signals can be the result of a Fg interaction with over-expressed astrocyte ICAM-1 and PrP C .…”
Section: Discussionsupporting
confidence: 88%
“…We used this method to observe interactions between Fg and its receptors ICAM-1 and PrP C on the surface of astrocytes. In a preliminary study, the use of a higher content of Fg (2 or 4 mg/mL), similar to those used in our previous studies [ 16 , 21 ], resulted in signal saturation. Therefore, we used lower doses of Fg to detect if there was an association of Fg with its astrocyte receptors.…”
Section: Resultsmentioning
confidence: 69%
See 3 more Smart Citations